Fake News Analysis on Supreme Court Decisions Relating to Law No. 11 of 2008 From Linguistic Forensic Perspective - Husni Thamrin; Dadang Sudana; Andika Duta Bachari; R. Dian Dia-An Muniroh (Jurnal Pendidikan Bahasa dan Sastra, 2023)
The purpose of this study is to analysis speech act form and speech event of a person from forensic linguistic perspective who break the rule of Law No. 11 of 2008 about Information and Electronic Transactions, Article 28 Paragraph (2), “Intentionally and Without Right Spread Information Intended to Induce Hate Speech or Hostility towards Certain Individuals and/or Community Groups Based on Ethnicity, Religion, Race, Group, and Intergroup (SARA).” This study used a desvriptive qualitative method. The data of conversation text includes identification, classification, analysis, and discussion. Participant who became the object of this research was a 54-year-old man who was accused of spreading fake news. The form of speech act data analysis refers to the theory of Austin Searle (1969), while speech events refer to Hymes (1972). The results of the research show that there are four speech acts, such as; assertive, directive, expressive, commissive, and declarative. The results of the research on speech events found eight speech events, starting from setting scene, participant, ending, action, instrumentality, key, norm, and genre.